2018
DOI: 10.1111/bor.12367
|View full text |Cite
|
Sign up to set email alerts
|

Middle to Late Pleistocene lake‐level fluctuations of Lake El'gygytgyn, far‐east Russian Arctic

Abstract: Lake El'gygytgyn, located in central Chukotka, Russian Arctic, was the subject of an international drilling project that resulted in the recovery of the longest continuous palaeoclimatic and palaeoenvironmental record for the terrestrial Arctic covering the last 3.6 million years. Here, we present the reconstruction of the lake-level fluctuations of Lake El'gygytgyn since Marine Isotope Stage (MIS) 7 based on lithological and palynological as well as chronological studies of shallow-water sediment cores and su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

5
1

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 46 publications
0
10
0
Order By: Relevance
“…2) may be explained by some wave actions and wind-induced currents in partly open water, leading to zero sedimentation or even minor erosion in the upper part of Unit A. Comparable (low) sedimentation rates have been discovered in the other arctic lakes (Fedorov et al 2019).…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…2) may be explained by some wave actions and wind-induced currents in partly open water, leading to zero sedimentation or even minor erosion in the upper part of Unit A. Comparable (low) sedimentation rates have been discovered in the other arctic lakes (Fedorov et al 2019).…”
Section: Resultsmentioning
confidence: 93%
“…Comparable (low) sedimentation rates have been discovered in the other arctic lakes (Fedorov et al . ).…”
Section: Resultsmentioning
confidence: 97%
“…Abundant planktonic diatoms led to low benthic/ planktonic diatom ratios throughout LUIV implying high lake levels during this time with limited habitat availability for benthic taxa (Heinsalu et al, 2007;Wang et al, 2011;Wolin and Stone, 2010). Lake-level reconstructions from El'gygytgyn have been used to imply that lake levels were high following MIS4 leading to the formation of a lacustrine terrace 9e11 m above the current lakelevel (Fedorov et al, 2019;Glushkova and Smirnov, 2007). Though the timing of the lake highestand was not effectively constrained due to the lack of a reliable age model at El'gygytgyn, high lake levels represented favourable conditions that occurred during MIS3 (Juschus et al, 2011).…”
Section: Evidence For a Mis3 Lake Highestandmentioning
confidence: 99%
“…Evidence for lake-level variability during the Holocene is seen by erosional truncation of acoustic reflectors belonging to AU2 and the pinching out of AU1 reflectors at water depths <10 m. The occasional absence of AU1 in the shallow outflow area is evidence of subaerial exposure of older sediments with subsequent erosion. Evidence from El'gygytgyn has suggested that lake levels during the Holocene were initially high but decreased progressively (Fedorov et al, 2019;Glushkova and Smirnov, 2007;Juschus et al, 2011). Recent lake-level variability is evidenced by the absence of significant deposition of AU1 on top of sediments in shallow areas.…”
Section: The Holocenementioning
confidence: 99%
“…Fedorov et al . () reconstructed the lake‐level fluctuations of Lake El'gygytgyn since MIS 7, using lithological and palynological as well as chronological data of shallow‐water sediment cores and subaerial lake terraces. The results suggest that the main triggers of lake‐level fluctuations are changes in air temperature and precipitation, with the former controlling the duration of the lake‐ice cover and the associated near‐shore sediment transport that blocks or opens the outflow.…”
mentioning
confidence: 99%